1992
DOI: 10.1200/jco.1992.10.7.1066
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized comparison of cisplatin alone or in combination with methotrexate, vinblastine, and doxorubicin in patients with metastatic urothelial carcinoma: a cooperative group study.

Abstract: Although a more toxic regimen, we found M-VAC to be superior to single-agent cisplatin with respect to response rate, duration of remission, and overall survival in patients with advanced urothelial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
401
1
21

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 922 publications
(439 citation statements)
references
References 21 publications
16
401
1
21
Order By: Relevance
“…For this reason, adjuvant systemic chemotherapy should be investigated because good objective responses are observed in a palliative setting [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, adjuvant systemic chemotherapy should be investigated because good objective responses are observed in a palliative setting [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with cisplatin, approved for the treatment of advanced disease in the early 1980s, doubled median survival to 8 months (Loehrer et al, 1992).…”
mentioning
confidence: 99%
“…4,5 However, this regimen has substantial side effects that can be life threatening: Nausea/emesis, neutropenia, neutropenic fever, mucositis, and renal insufficiency have been reported in a significant proportion of patients, with some toxic deaths reported. 3,4,6 In a recently published trial, a reduced incidence of hematologic and nonhematologic toxicities was reported with the gemcitabine-cisplatin combination compared with M-VAC, although only patients with a good PS and normal renal function were included. 18 New combination regimens have been tested in Phase II studies.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized trials have shown that the M-VAC regimen was superior compared with single-agent cisplatin 4 and compared with the combination of cisplatin, methotrexate, vinblastine, and doxorubicin 5 both in terms of response rates and survival. However, very few patients are long-term survivors, 6 and the toxicities are significant: Grade 3-4 nausea and emesis, 12%; Grade 3-4 neutropenia, 24 -58% (with febrile neutropenia in 10 -25% of patients); severe mucositis, 13-17%; renal failure, 7%; and toxic deaths, 3%.…”
mentioning
confidence: 99%
See 1 more Smart Citation